THE EFFECT OF ONION (Allium sativum) EXTRACT TO TREAT TILAPIA FRY (Oreochromis niloticus) WITH BACTERIAL INFECTED Aeromonas hydrophila - Ani Lestari; Nurliah; Baiq Hilda Astriana (Journal of Fish Health, 2021)
Research on the effect of garlic extract (allium sativum) to treat tilapia (oreochromis niloticus) seeds which are infected with aeromonas hydrophila bacteria. This research was conducted for 14 days from 18 December to 31 December 2019 which took place at the Wet Laboratory of the Aquaculture Study Program, Mataram University, West Nusa Tenggara (NTB). This study used a completely randomized design (CRD) with an experimental method consisting of 5 treatments and 3 replications. The container used in this study was a 15 liter jar with a volume of 10 liters. The containers used are 15 units, where in treatment one (P1) using without soaking garlic extract and without being infected with Aeromonas hydrophila bacteria, treatment two (P2) without soaking garlic extract and being infected with Aeromonas hydrophila bacteria, (P3) using soaking onion extract white with a concentration of 1% and infected with Aeromonas hydrophila bacteria, (P4) using garlic extract immersion with a concentration of 1.5% and infected with Aeromonas hydrophila bacteria, (P5) using garlic extract immersion with a concentration of 2% and infected with Aeromonas hydrophila bacteria. The parameters observed during the study included survival rate (SR), relative percent survival (RPS), observation of clinical symptoms, and water quality. The results showed that giving garlic extract with different concentrations had a significantly different effect on survival rates and relative percent survival (RPS).